Effects of Multimedia Education Integrated Marketing Course Teaching on Students’ Marketing Awareness and Marketing Attitude - Tsai, Wen-Jung; Yao, Shuen-Huei (International Journal of Emerging Technologies in Learning (iJET), 2023)
Integrating information technology into teaching will be a major policy for schools, improving teaching models. Teachers should get rid of the traditional teaching model of merely stressing on knowledge imparting in order to have students enjoy learning, absorb knowledge, and cultivate interests. With an experimental design model, 116 students of the Department of Business Administration of a university in southern Taiwan are participating in the quasiexperimental research. The experimental class (58 students) is preceded by multimedia education integrated marketing course teaching, and the control class (58 students) maintains traditional teaching combined marketing course teaching for the 18-week (three hours per week for a total of 54 hours) experimental teaching research. According to the results of the proposed discussions and suggestions, it is expected to develop instruction from a single model to an intuitive, interesting, artistic, and three-dimensional mode, create a vivid and interesting teaching situation for students, getthem into a lively learning atmosphere, induce students’ attention, and enhance students’ learning interests.